Regionalism in a multilateral world - Wilfred Ethier (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
Recent regional initiatives have been addressed from a Vinerian perspective of regional integration as a combination of trade creation and trade diversion. This is true both of policy-oriented economists, who tend to be critical of the initiatives, and of theorists, who have added dynamic and game-theoretic elements to the Vinerian structure. This paper describes the stylized facts of much recent regional integration, and develops an alternative model. The analysis suggests the possibility that regional integration, far from threatening multilateral liberalism, may in fact be a direct consequence of the success of past multilateralism and an added guarantee for its survival.
Keywords: F15; F13; F23; 330; Direct investment; regionalism; multilateralism; policy reform